2007
DOI: 10.1111/j.1574-6968.2007.00923.x
|View full text |Cite
|
Sign up to set email alerts
|

Copper deficiency in potato dextrose agar causes reduced pigmentation in cultures of various fungi

Abstract: Potato dextrose agar (PDA) is one of the most commonly used media for the isolation and cultivation of fungi, with morphological features and pigmentation in culture often being important for identification of cultures. Cultivation of various fungi on different brands and batches of powdered (commercial) potato dextrose media revealed deficient pigmentation in five of 10 media tested. Reduced pigmentation on these media was correlated with low levels of copper and colony colour was restored by the addition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 19 publications
(28 reference statements)
2
27
0
7
Order By: Relevance
“…In Gaeumannomyces graminis , addition of copper to the medium results in dark cultures and the cells have a layer of melanin in the cell wall visible by TEM (Caesar-Tonthat et al 1995). Similarly, variation in copper levels among commercial fungal media (potato dextrose agar) correspond to variable pigmentation in multiple fungal species including Trichoderma harzianum , Stachybotrys atra , Fusarium culmorum , and Cladosporium herbarum (Griffith et al 2007). Molecular studies also highlight the importance of copper in melanization.…”
Section: Melanin Biosynthesismentioning
confidence: 99%
“…In Gaeumannomyces graminis , addition of copper to the medium results in dark cultures and the cells have a layer of melanin in the cell wall visible by TEM (Caesar-Tonthat et al 1995). Similarly, variation in copper levels among commercial fungal media (potato dextrose agar) correspond to variable pigmentation in multiple fungal species including Trichoderma harzianum , Stachybotrys atra , Fusarium culmorum , and Cladosporium herbarum (Griffith et al 2007). Molecular studies also highlight the importance of copper in melanization.…”
Section: Melanin Biosynthesismentioning
confidence: 99%
“…The importance of copper in melanization has been highlighted in a few studies; this importance is likely due to the requirement of copper as a cofactor for laccases (30,31). In A. nidulans, a mutation in the ygA gene that encodes a transporter produces yellow conidia at high pH and green conidia at low pH (32,33).…”
mentioning
confidence: 99%
“…In general, wild-type strains grow faster than AT01 under the same concentration of copper. Griffith et al (2007) also found that adding copper to potato/dextrose/agar exerts a significant impact on the growth of fungi. Furthermore, the incubation time increases along with the growth of wild-type strains when the copper exceed 2.1 mM.…”
Section: Copper Accumulation Properties Of Strain At01mentioning
confidence: 98%